Standards and quality controls for information technology applications to serve the Holy Quran (Journal Of Educational and Psychological Researches, 2015)
the research goal is preparing a list of standard criteria and quality controls for information technology applications to serve the Holy Quran.To achieve this goal, the researcher has built a list of criteria according to the following steps:First - identify the key areas covered by the whole list which are:1 – Standards of system building and implementing with the operating screens.2 – Standards of display forms including audio and video presentation.3 – Standards which are related to the program philosophy.4 - Standards which are related to the program objectives.5 - Standards which are related to the program content.6 - Standards which are related to sources and learning strategies.7 - Standards which are related to the program educational activities.8 - Standards which are associated with the amending and immediate feedback.9 - Standards which are associated to the learners.10 - Standards which are related to the methods of interaction between the learner and the program.11 - Standards which are related to technical aspects.12 - Standards which are related to the administrative aspects of the production.Secondly - the formulating of items: The researcher formulated items standard according to the areas they represent, and organized them in the form of a closed questionnaire which were in their first form like (17, 22, 18, 27, 33, 12, 15, 21, 23, 14, 19, 11) items. There items were arranged respectively according to their areas to become (232).       And the resolution was presented to a group of educational arbitrators and specialists in technology, curriculum, teaching methods, educational technology, measurement and evaluation in Iraqi universities to determine the validity of each item and its suitability according its area. The researcher used three choices for each item (appropriate, inappropriate, need to be modified), and asked them to propose other additional items if it is required. The researcher has shown the experts that the arbitration process will be achieved according to the Delphi method of all three rounds to reach the highest level of scientific accuracy.           The resolution has been processed by calculating the weighted average of each item in addition to the weight percentile according to the Fisher equation. All the items have an average above the value and a high weighted percentage in general. The items were re-ordered depending on the strength of each item and the value of Centennial weight. The expert mentioned observations and suggestions to amending item(s) or dissociate some of the items into two items. In addition to integrate some other items and delete others bringing the number of items to (210).             Then the researcher transfer list of criteria to card calendar specific measured each item weight listed on the ladder graded four (excellent, very good, good, poor) were given weights following (0, 1, 2, 3) to evaluate the quality control standards for IT applications programmed To serve the Holy Quran.The researcher codified items card in order to make sure its Validity to the attention of a number of arbitrators specialists in the field of technology and curriculum and teaching methods and educational technology and measurement and evaluation to express their point of view about the clarity of each item and whether they are true in the measure placed for him, has expressed Important Notes and the value of satisfied researcher by and conducted against which the necessary adjustments, bringing the number of items observation card (204) item have been calculated researcher Reliability of the card across individuals using the method of Cooper to calculate the coefficient of agreement between the observers and that counts the number of times the agreement and the number of times the difference between the observers, it is clear that all transactions fortitude to analyze researcher with the observed first , The researcher observed with the second, and first observed with the second Notably, a high rank as follows (84.8%, 86.9%, 89.7%), and this means that the analysis tool was a high level of consistency, which gives an indication of the possibility of using the tool.       The researcher has developed some recommendations and a number of proposals to complement the current study.